To make you feel my love - Joel, Billy; Asher, Peter; Nicolo, Joe'The Butcher'; Sony Music Entertainment (New York : Sony Music Entertainment, 1997)
Contains a track taken from the album Billy Joel: The Greatest Hits Volume III.
CD 1 : To Make You Feel My Love.
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English